Novel (3+2) dipolar cycloadditions of pyridinium ylides - Tongue, Tom (2017)
This thesis describes advances in novel (3+2) dipolar cycloadditions of pyridinium ylides, their reactions with electrophilic alkenes afford tetrahydroindolizines which can possess alkaloid-like scaffolds. Pyridinium ylides have been shown to be highly reactive intermediates that are able to rapidly generate molecular complexity with excellent regio and diastereoselectivity. Chapter one reports an introduction on the chemistry of pyridinium ylides and introduces spirocyclic indolizidine containing natural products which could conceivably be synthesised through (3+2) dipolar cycloadditions. The results and discussion section is divided into three chapters: Chapter two describes the synthesis of indoxyl dipolarophiles including a novel approach towards the synthesis of 2-alkenylindol-3-ones. Details of the reactions of these dipolarophiles with pyridinium ylides to afford spirocyclic indoxyl cycloadducts follow. Subsequent modification of the 1,2-dihydropyridine moiety in the resulting cycloadducts is also demonstrated; Chapter three describes the investigation towards an asymmetric (3+2) dipolar cycloaddition, using pyridinium ylides generated by the in situ decomposition of diazo compounds with transition metal catalysts; Finally, chapter four describes attempts to synthesise spirocyclic indoxyl compounds which are structurally related to the opioid mitragynine pseudoindoxyl. Initially this is investigated via the methodology developed in chapter two, then subsequently using a magnesium iodide promoted ring expansion of a cyclopropane.